KESADARAN WP DAPAT MEMODERASI MODERNISASI SISTEM ADMINISTRASI, PEMAHAMAN PERPAJAKAN, SANKSI DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Jessica; Ngadiman (Fakultas Ekonomi Universitas Tarumanagara, 2024)
The purpose of this study was to analyze the effect of modernization of the administrative system, understanding oftaxation, sanctions and service quality individually and simultaneously on MSME taxpayer compliance in the city ofSambas, West Kalimantan. This study uses a quantitative approach by conducting a survey of MSME taxpayers inthe city of Sambas. The population in this study were MSME taxpayers as many as 14,463 taxpayers and a sample of99 people using a non-probability sampling quota sampling technique. The data collection method used aquestionnaire with a Likert scale of 1-4 points. The data analysis methods used include: Data Quality Test,Assumption Test, Moderation Regression Test, and Hypothesis Testing. The results showed that the modernizationof the administrative system had a positive and significant effect on MSME taxpayer compliance in the city ofSambas, understanding of taxation had a positive and significant effect on the compliance of MSME taxpayers in thecity of Sambas, Sanctions had a positive and significant effect on the compliance of MSME taxpayers in the city ofSambas, Quality service has a positive and significant effect on MSME taxpayer compliance in the city of Sambas,and taxpayer awareness strengthens the influence of modernization of the administrative system, understanding oftaxation, sanctions and service quality on MSME taxpayer compliance in the city of Sambas, West Kalimantan.